Micro-CT, Mechanical, and Histological Examination of the Effect of Local Adjuvants on Porcine Cortical Bone Following Intralesional Curettage of Bone Tumors - Apostolopoulos, Vasileios; Boháč, Petr; Marcián, Petr; Zambo, Iva Staniczkova; Pazourek, Lukáš; Mahdal, Michal; Neradil, Jakub; Návrat, Tomáš; Tomáš, Tomáš (Annals of surgical oncology, 2024)
BACKGROUND AND OBJECTIVES: Curettage is the removal of a tumor from the bone while preserving the surrounding healthy cortical bone, and is associated with higher rates of local recurrence. To lower these rates, curettage should be combined with local adjuvants, although their use is associated with damage to nearby healthy bone. OBJECTIVE: The purpose of this analysis is to determine the effect of local adjuvants on cortical porcine bone by using micro-computed tomography (micro-CT) along with histological and mechanical examination. METHODS: Local adjuvants were applied to porcine specimens under defined conditions. To assess changes in bone mineral density (BMD), a micro-CT scan was used. The pixel gray values of the volume of interest (VOI) were evaluated per specimen and converted to BMD values. The Vickers hardness test was employed to assess bone hardness (HV). The depth of necrosis was measured histologically using hematoxylin and eosin-stained tissue sections. RESULTS: A noticeable change in BMD was observed on the argon beam coagulation (ABC) sample. Comparable hardness values were measured on samples following electrocautery and ABC, and lowering of bone hardness was obtained in the case of liquid nitrogen. Extensive induced depth of necrosis was registered in the specimen treated with liquid nitrogen. CONCLUSION: This study determined the effect of local adjuvants on cortical bone by using micro-CT along with histological and mechanical examination. Phenolization and liquid nitrogen application caused a decrease in bone hardness. The bone density was affected in the range of single-digit percentage values. Liquid nitrogen induced extensive depth of necrosis with a wide variance of values.
Keywords: kostní denzita; Animals; Bone Density; kortikální kost; kyretáž; Curettage; zvířata; X-Ray Microtomography; rentgenová mikrotomografie; prasata; Swine; Bone Neoplasms; nádory kostí; Cortical Bone